The American century in Europe - Moore, R. Laurence (Robert Laurence), 1940-; Vaudagna, Maurizio (Cornell University Press, 2003)
The notion of an American Century has fallen out of favor in recent years-historians prefer to focus on the United States as part of a transatlantic community. The contributors to this volume edited by R. Laurence Moore and Maurizio Vaudagna seek to understand how the exercise of American power was in crucial ways shaped and limited by the historic ties of the United States to Europe. They evaluate the impact of the "American Century" (as publisher Henry R. Luce named it in 1941) from Woodrow Wilson's dream of a new world order, to Cold War economic policies, to more recent American cultural imperialism and its immediate descendent, American-led globalization. The American Century in Europe gathers an international group of scholars who explore the ways twentieth-century American power (diplomatic, cultural, and economic) has been felt across the Atlantic. The authors demonstrate that the American Century was marked less by American hegemony than by reciprocal influence between the United States and Europe. The scale of American wealth certainly guaranteed influence abroad, but as the essays demonstrate, the American thirst for trade just as surely opened America's borders to cultures from around the world